mRNA decay is regulated via sequestration of the conserved 5'-3' exoribonuclease Xrn1 at eisosome in yeast - Vaškovičová, Katarína; Awadová, Thuraya; Veselá, Petra; Balážová, Mária; Opekarová, Miroslava; Malinsky, Jan (European journal of cell biology, 2017)
We describe a novel mechanism of mRNA decay regulation, which takes place under the conditions of glucose deprivation in the yeast Saccharomyces cerevisiae. The regulation is based on temporally stable sequestration of the main 5'-3' mRNA exoribonuclease Xrn1 at the eisosome, a plasma membrane-associated protein complex organizing a specialized membrane microdomain. As documented by monitoring the decay of a specific mRNA substrate in time, Xrn1-mediated mRNA degradation ceases during the accumulation of Xrn1 at eisosome, but the eisosome-associated Xrn1 retains its functionality and can be re-activated when released to cytoplasm following the addition of glucose. In cells lacking the eisosome organizer Pil1, Xrn1 does not associate with the plasma membrane and its activity is preserved till the stationary phase. Thus, properly assembled eisosome is necessary for this kind of Xrn1 regulation, which occurs in a liquid culture as well as in a differentiated colony.
Keywords: RNA Stability; Saccharomyces cerevisiae; messenger RNA; membránové proteiny; Exoribonucleases; Xrn1; Membrane Proteins; exoribonukleasy; Phosphoproteins; Cell Membrane; fosfoproteiny; Saccharomyces cerevisiae Proteins; Saccharomyces cerevisiae - proteiny; mRNA decay regulation; cytoplazma; RNA, Messenger; membránové mikrodomény; Eisosome; Membrane Microdomains; Pil1; buněčná membrána; multiproteinové komplexy; Cytoplasm; Multiprotein Complexes; Plasma membrane compartmentalization; stabilita RNA